14:45
@MatheinBoulomenos no I was correcting myself
@MatheinBoulomenos is there a conceptual proof that $H^1\operatorname{Hom}_G(\Bbb Z,-^G) \cong \operatorname{Hom}(G,-^G)$?
and what I'm saying is $H^1\operatorname{Hom}_G(\Bbb Z,\operatorname{Hom}_G(\Bbb Z,-)) \cong \operatorname{Hom}(G,\operatorname{Hom}_G(\Bbb Z,-))$
and I'm not sure how tensor works
at least I can't convert the right hand side into a tensor since $G$ is non-abelian
in the meantime let's revisit how Galois descent is Morita equivalence
we have two categories: $L[G,1]$-Mod and $K$-Mod
$V \mapsto V^G$, $W \mapsto L \otimes_K W$
$L$ is an ($L[G,1]$, $L$)-bimodule
now we claim that $L[G,1] \cong \operatorname{End}_K(L)$ where the forward map is tautological
maybe $V^G = L \otimes_{L[G,1]} V$
by Watts theorem, if it is a tensor, it would be $L[G,1]^G \otimes_{L[G,1]} V$
I don't think even $L[G,1]^G$ makes sense but let's see
actually it might make sense
$G$ acts on $L[G,1]$ by composition: $\sigma \cdot f = \sigma \circ f$
so in terms of $\operatorname{Hom}(L,L)$ that's acting on the right factor only
wait, then we can use the trivial action on $L$
so it's $\operatorname{Hom}(L_t, L)$
and we can use the famous equation $\operatorname{Hom}(L_t,L)^G = \operatorname{Hom}_G(L_t,L)$
by choosing a basis we have $\operatorname{Hom}(L_t,L)^G = \operatorname{Hom}_G(K,L)^n$
18 mins ago, by
Leaky Nun maybe $V^G = L \otimes_{L[G,1]} V$
so we're back to this, where $G$ acts trivially on $L$
I should be more careful with the non-canonical basis choosing
$\operatorname{Hom}(L_t,L)^G = \operatorname{Hom}_G(L_t,L) = \operatorname{Hom}(L_t,L^G) = \operatorname{Hom}(L,K)$
yeah it's $L^\ast$ instead
so $V^G = L^\ast \otimes_{L[G,1]} V$?
you know what, $V^G = \operatorname{Hom}_{L[G,1]}(L,V)$
$v \mapsto (b \mapsto bv)$
$\varphi \mapsto \varphi(1)$
$\varphi((\sum a_\sigma \sigma) b) = (\sum a_\sigma \sigma) \varphi(b)$
maybe I should take the invariant quotient
I need to quotient by the ideal generated by $\sigma - 1$
does this even make sense
$\sum a_\sigma \sigma \mapsto \sum a_\sigma$
congratulations all you get is $L$
we need $\varphi_v(\sigma b) = \sigma \varphi_v(b)$
$\sum a_\sigma \sigma \mapsto \sum a_\sigma$ isn't $L[G,1]$-linear
if you quotient by a left ideal you don't get a ring right
do we even have $V = \operatorname{Hom}_{L[G,1]}(L[G,1], V)$
so the rule is that if $M$ is an $(R,S)$-bimodule and $N$ is an $(R,T)$-bimodule then $\operatorname{Hom}_R(M,N)$ is an $(S,T)$-bimodule?
$s\varphi t: m \mapsto \varphi(ms)t$
$((s_1 s_2)\varphi)(m) = \varphi(m s_1 s_2) = (s_1(s_2 \varphi))(m)$
$(\sigma - 1)b = \sigma(b) \sigma - b$
$\varphi(\sum a_g g) = \sum a_g g(v) = \sum a_g v$
let's check $V = \operatorname{Hom}_{L[G,1]}(L[G,1], V)$
this might be troublesome
$\varphi_v(\sum a_g g) = \sum a_g g(v)$
we need $(\sum a_g g)(b) = \sum a_g g(b)$
that's where I went wrong
$L[G,1]$ don't act trivially on $L$
so indeed $V^G = \operatorname{Hom}_{L[G,1]}(L,V)$
now what does this look like in terms of $\operatorname{End}_K(L)$
$L$ is a left $\operatorname{End}_K(L)$-module
$V^G = \operatorname{Hom}_{\operatorname{End}_K(L)}(L,V)$
$v \mapsto (b \mapsto bv)$
4 mins ago, by
Leaky Nun so indeed $V^G = \operatorname{Hom}_{L[G,1]}(L,V)$
I haven't checked the opposite direction
$g\varphi(1) = \varphi(g(1)) = \varphi(1)$
$v \mapsto \varphi_v$ where $\varphi_v(b) := bv$
then $\varphi_v (\sum a_g g(b)) = \sum a_g g(b) v = \sum a_g g(b) g(v) = \sum a_g g(bv) = (\sum a_g g) \varphi_v(b)$
we need to be able to project from $V$ to $V^G$
so we need a map $\operatorname{Hom}_{L[G,1]}(L[G,1],V) \to \operatorname{Hom}_{L[G,1]}(L,V)$
by Yoneda this means we need $f: L \to L[G,1]$
such that $f((\sum a_g g) b) = (\sum a_g g) f(b)$
i.e. we need $f(g(b)) = g \cdot f(b) = g(f(b)) \cdot g$ and $f(b_1 b_2) = b_1 \cdot f(b_2)$
how is this done in the char 0 case where we can just take $v \mapsto \frac1n \sum gv$
take $\varphi \in \operatorname{Hom}_{L[G,1]}(L[G,1],V)$
then $\varphi' \in \operatorname{Hom}_{L[G,1]}(L,V)$ is given by $\varphi'(b) = b \frac1n \sum g\varphi(1) = b \varphi(\frac1n \sum g)$
so for $V=L[G,1]$ and $\varphi = 1$ we have $\varphi'(1) = \frac1n \sum g$
oh ok this isn't impossible